Performance management maturity in a federal regulatory agency - Coelho Junior, Francisco Antonio; Meneses, Pedro Paulo Murce; Silva-Filho, Antônio Isidro da; Fonseca, Diogo Ribeiro da (Revista de Administração da UFSM, 2018)
The present paper aims to describe the maturity level of institutional and individual performance management (PM) practices in a federal regulatory agency. Three Technical Groups (TGs) were formed with public servants from three different careers and an interview schedule was applied with questions concerning the PM maturity level in the organization. The answers were registered and thematic content analysis was applied as a mean to interpret data. The results identify performance management in a uncertainty, lack of standards and unsystematic level. Factors such as the role of leaderships, informal communication and the shared attitudes and perceptions towards the importance of the PM, have showed to be relevant for its maturation in organizational departments. Given the conclusions and variables identified in this study, we recommend the realization of a survey in the organization to measure attitudes towards performance management. We also recommend, in future research, the consideration of variables referring to the organizational structure, which may offer support to the comprehension of the maturity level as a contextual variable in the organization.